2020
DOI: 10.1002/bies.202000099
|View full text |Cite
|
Sign up to set email alerts
|

How everyday sounds can trigger strong emotions: ASMR, misophonia and the feeling of wellbeing

Abstract: We propose that synesthetic cross-activation between the primary auditory cortex and the anatomically adjacent insula may help explain two puzzling conditionsautonomous sensory meridian response (ASMR) and misophonia-in which quotidian sounds involuntarily trigger strong emotional responses. In ASMR the sounds engender relaxation, while in misophonia they trigger an aversive response. The insula both plays an important role in autonomic nervous system control and integrates multiple interoceptive maps represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 79 publications
2
32
0
Order By: Relevance
“…As highlighted in McGeoch and Rouw ( 2020 ), the often highly specific nature of trigger sounds (i.e., repetitive, low frequency, etc.) points to the involvement of bottom-up mechanisms, while the complex behavioral and emotional responses suggest involvement of higher-level (top-down) processes.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted in McGeoch and Rouw ( 2020 ), the often highly specific nature of trigger sounds (i.e., repetitive, low frequency, etc.) points to the involvement of bottom-up mechanisms, while the complex behavioral and emotional responses suggest involvement of higher-level (top-down) processes.…”
Section: Discussionmentioning
confidence: 99%
“…Machine-related sounds are also common, such as those emitted by the computer keyboard, the ticking of the clock, the coffee maker, the stapler, or hair dryers, among others [ 21 ]. These are some examples, but it should be noted that triggering sounds are very varied and, although they are usually everyday [ 24 , 32 ], they are influenced by the context and the individual characteristics of the patient [ 27 ]. Recent research has found that the triggering stimulus can have different sensory modalities, not limited to sound alone [ 5 , 28 , 33 ].…”
Section: Results Of the Bibliographic Researchmentioning
confidence: 99%
“…To have a better understanding of the causes of misophonia, it should be taken into account that there may be individual differences that determine that only a group of people develop this aversion to sounds. This specificity of stimuli and symptomatology could be due to neurobiological alterations [ 1 , 2 , 10 , 32 , 39 , 45 , 46 , 47 , 48 , 49 ], and/or genetic predisposition [ 20 , 23 , 40 , 41 , 43 ], which, in conjunction with learning or conditioning [ 3 , 4 , 24 , 35 , 52 , 53 , 56 ], result in the development of misophonia. From this it can certainly be concluded that in order to understand the etiology of this disorder, it is essential to approach it from a multifactorial perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that experiencing ASMR may lead to a temporary reduction in pain perception in ASMR experiencers, which is in line with prior findings of beneficial properties of ASMR in terms of pain reduction among ASMR experiences with chronic pain (Barratt & Davis, 2015). A likely mechanism for this is parasympathetic activation of the autonomic nervous system (ANS) by ASMR, as described by McGeoch and Rouw (2020), who propose that ASMR can increase vagal tone through parasympathetic activation. More established methods of reducing pain, such as deep breathing (see Busch et al, 2012), have a similar parasympathetic activation profile, and it is likely that ASMR influences pain in a similar way.…”
Section: Discussionmentioning
confidence: 99%